Myelolipoma of the posterior mediastinum in a patient with chronic dyserythropoietic anemia - Cristiano Claudino Oliveira; Gilmar Felisberto Junior; Viviane Hellmeister Camolese; Erica Nishida Hasimoto; Daniele Cristina Cataneo; Antônio José Maria Cataneo; Julio De Faveri (University of São Paulo, 2016)
Myelolipoma (ML) is an uncommon benign mesenchymal neoplasia composed of mature adipose and hematopoietic tissues of uncertain etiology. Less than 3% of MLs occur in the mediastinal topography. The main differential diagnosis involves extramedullary hematopoiesis; therefore, pathological evaluation is essential for the definitive diagnosis. The authors report the case of a 50-year-old man diagnosed with congenital dyserythropoiesis and secondary hemosiderosis, who presented a posterior mediastinal tumor. The tumor was resected. It was macroscopically characterized by mature fat tissue with fibrous areas and soft consistency, which was yellowish at the cut surface. Histology revealed a well-defined nodule composed of adipocytes and hematopoietic tissue represented by erythroid, granulocytic, and megakaryocytic series, which was consistent with the diagnosis of ML located in the posterior mediastinum. There was no recurrence of the lesion during the 3-year follow-up. The aim of this report is to show the diagnosis of an unusual mediastinal lesion in the context of a chronic hematologic disease